Host suitability of three avocado cultivars (Persea americana Miller: Lauraceae) to oriental fruit fly (Bactrocera (invadens) dorsalis (Hendel) (Diptera: Tephritidae)). (December 2016) - Ware, Anthony B.; du Toit, C.L. Neethling; du Toit, Erica; Collins, Richard; Clowes, Robert; Ekesi, Sunday; Mohamed, Samira A.
Abstract: The oriental (invasive) fruit fly Bactrocera ( invadens ) dorsalis (Hendel) (Diptera: Tephritidae) has invaded Africa and is currently established in over 30 countries and has caused in massive fruit losses. Avocado ( Persea americana Miller) is among the fruit with which the pest is associated. The aim of the study was to determine the host status of a 'black-skinned' cultivar "Hass" and two 'green-skinned' cultivars "Pinkerton" and "Fuerte" to B. ( invadens ) dorsalis . In the laboratory study conducted in Kenya in 2012 and 2013, punctured and unpunctured recently-harvested fruit were exposed to sexually-mature fruit fly in 'no-choice' experiments. B. ( invadens ) dorsalis readily developed in the punctured fruit but not in the uncompromised fruit (fruit not damaged by insects or handling). This result was confirmed in Tanzania in 2013 where flies were introduced to unpunctured fruit. In the field studies the fruit of each cultivar were caged in situ with flies for 72 h. On dissection only fruit damaged by false codling moth ( Thaumatotibia leucotreta (Meyrick)) were found to harbor B. (invadens) dorsalis . In the light of these results the risk imposed for "Hass", "Pinkerton" and "Fuerte" by B. ( invadens ) dorsalis is negligible under standard export conditions. The findings of this study and the implications to regional and international trade are discussed. Highlights: Black-skinned "Hass" and green-skinned "Fuerte" and "Pinkerton" were compared. Physiologically mature damaged avocado are potential hosts of oriental fruit fly. Undamaged physiologically mature avocado are not hosts of oriental fruit fly. Negligible risk of finding oriental fruit fly in avocado in exports.